ANALISIS DAN KONSEP PENGELOLAAN SUMBER DAYA ALAM DAN ZAKAT SEBAGAI KEBIJAKAN FISKAL SYARIAH UNTUK KESEJAHTERAAN RAKYAT DI INDONESIA - RUDIANTO, SOFIAN; TANJUNG, HENDRI; AYUNIYYAH, QURROH (Kasaba, 2023)
This research is entitled the analysis and concept of natural resource management and zakat as sharia fiscal policy for the welfare of the people in Indonesia. The background of this research is because of the writer's anxiety to see Indonesia as a country rich in natural resources and great potential for zakat, but many people still live in poverty. On the other hand, the state continues to rely on taxes as the main source of state revenue. This study wants to know how the concept of natural resource management and zakat in sharia fiscal policy and the extent to which the management of natural resources and zakat in sharia fiscal policy are able to realize people's welfare. For this reason, the research method taken by the author is analytical descriptive. In this study, it was found that the potential for state revenue is very large (Rp 18,918 trillion) from natural resources if managed based on sharia, namely all natural resources in the form of mining, energy, water for the public and forests managed by the state, so that all the results will be state revenue. This revenue potential will be even greater (Rp 19,246 trillion) if zakat, which has a potential revenue of Rp 327.6 trillion, is also managed by the state directly. With this huge revenue potential, it is certain to be able to realize the welfare of the people. The indicator of people's welfare is ensuring the fulfillment of the basic needs of each individual (clothing, food and housing) as well as the fulfillment of the people's basic needs (education, health and security).